Surveillance and management of ventriculitis following neurosurgery. Issue 4 (April 2015) - Humphreys, H.; Jenks, P.J.
Summary Ventriculitis is an important complication following neurosurgery and is often associated with the use of an external ventricular drain (EVD). The incidence varies from <5% to 20%, partly due to variations in the definitions used for diagnosis. Staphylococci are the most important causes but the isolation of coagulase-negative staphylococci from a cerebrospinal fluid (CSF) sample needs to be interpreted with caution as it may represent contamination. Risk factors for ventriculitis include advanced age, the duration of EVD placement, the number of manipulations and the presence of intraventricular haemorrhage. Prevention strategies increasingly focus on the implementation of a care bundle that includes aseptic technique at the time of insertion and during any manipulations, skin preparation, prophylactic antibiotics, and appropriate dressings at the site of the EVD. The use of EVDs impregnated with antimicrobial agents is increasing but, whereas some studies show that these are effective, it is not clear whether they provide added benefit when there is compliance with other measures. Antimicrobial treatment is challenging as many widely used agents do not penetrate into the CSF and causative bacteria are increasingly multidrug resistant. Often a combination of high-dose intravenous and intraventricular agents is required, especially for Gram-negative infections. Large trials in this area are challenging to conduct; therefore, to better inform preventive strategies and to optimize management of this important condition, ongoing national surveillance and pooling of data on treatment approaches and outcomes are needed.